Pendampingan Perencanaan Partisipatif Program Tabungan dan Patungan Kurban Guna Meningkatkan Minat Berkurban di Masa Pandemi - Muhamad Subhi Apriantoro; Rafiq Ahmad Zaky; Vivin Dwi Febrianti (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
This service activity is carried out to bridge the importance of saving and sacrificial facilities for Muslim congregations from the As-Shaykh Jabir Al-Faifi Mosque, Ngasem Village, Colomadu District, Karanganyar Regency, Central Java. Assistance is carried out by previously holding deliberations with the Mosque Prosperity Council to prepare a design for a savings and joint sacrifice scheme which will then be disseminated to local Muslims through the Rukun Neighbor forum and studies at the mosque. The method used to explore and understand the couple's problems is an observation of related informants and documentation. Data analysis used triangulation of data sources. The results of this activity indicate that there is an increase in the enthusiasm of residents in carrying out Qurban worship after the existence of savings products and qurban joint ventures, as can be seen from the increase in the registration of Qurban participants by 60%.